2022
DOI: 10.1001/jamaoto.2021.3567
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Cancer Incidence and Mortality Trends in All 50 States in the US, 2001-2017

Abstract: IMPORTANCE Oropharyngeal cancer (OPC) incidence is rising among men in the US. Comprehensive assessments of nationwide trends in OPC incidence and mortality by demographics, tumor characteristics at diagnosis, and geography are lacking.OBJECTIVE We examined secular trends in OPC incidence and mortality rates in all 50 US states and the District of Columbia (DC). DESIGN, SETTING, AND PARTICIPANTSIn this cross-sectional study, we used the US Cancer Statistics data set to examine OPC incidence trends from 2001 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 39 publications
2
61
1
Order By: Relevance
“…Oropharyngeal cancer accounts for 0.5% of all solid malignancies, and the incidence of oropharyngeal cancer has increased during the past three decades in the United States (US) [ 1 , 2 ]. A study investigating all 50 states of the US reported that oropharyngeal cancer increased by an average of 2.7% per year for men and 0.5% for women from 2001 to 2017 [ 3 ]. The rise in the incidence of oropharyngeal cancer is mainly due to an increase in human papillomavirus (HPV) prevalence and HPV-related oropharyngeal cancer [ 1 , 4 ].…”
Section: Background For the Deintensification Of Hpv-related Orophary...mentioning
confidence: 99%
See 1 more Smart Citation
“…Oropharyngeal cancer accounts for 0.5% of all solid malignancies, and the incidence of oropharyngeal cancer has increased during the past three decades in the United States (US) [ 1 , 2 ]. A study investigating all 50 states of the US reported that oropharyngeal cancer increased by an average of 2.7% per year for men and 0.5% for women from 2001 to 2017 [ 3 ]. The rise in the incidence of oropharyngeal cancer is mainly due to an increase in human papillomavirus (HPV) prevalence and HPV-related oropharyngeal cancer [ 1 , 4 ].…”
Section: Background For the Deintensification Of Hpv-related Orophary...mentioning
confidence: 99%
“…However, recent evidence has revealed a shift in disease burden to older age. In an epidemic study investigating all 50 states in the US, it was found that the incidence among men increased over 3% annually in a cohort of subjects aged ≥65 years between 2001 and 2017 [ 3 ]. Men aged 45–64 years showed a plateau after 2014.…”
Section: Recent Changes In Patient Characteristics and Deintensificationmentioning
confidence: 99%
“…For example, HPV vaccination coverage among males aged 19–26 years and Hispanic females aged 19–26 years increased, but approximately 50% of females aged 19–26 years and 70% of males aged 19–26 years remained unvaccinated [ 5 ]. Disparities in HPV vaccination coverage and HPV-cancer incidence exist in geographic locations in the United States [ 6 , 7 , 8 ]. Specifically, those living in rural areas [ 8 ] and in the Southern United States [ 6 , 7 ] have lower HPV vaccination rates and higher HPV-related cancer incidence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in HPV vaccination coverage and HPV-cancer incidence exist in geographic locations in the United States [ 6 , 7 , 8 ]. Specifically, those living in rural areas [ 8 ] and in the Southern United States [ 6 , 7 ] have lower HPV vaccination rates and higher HPV-related cancer incidence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 260,000 OPC cases were identified from 2001 through 2017 in the United States alone [ 6 ]. The incidence of HPV-associated OPCs has increased at a rate of 30% a year [ [1] , [2] , [3] ].…”
Section: Introductionmentioning
confidence: 99%